(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Introduction: Cervical cancer is a leading cause of death among women of reproductive age worldwide, with higher mortality among those lacking follow-up after detection of precancerous lesions. A major factor contributing to mortality is inadequate awareness regarding its preventability, available screening options, and HPV vaccination. Understanding barriers to screening is essential to promote early detection. Objectives: To assess knowledge and awareness about cervical cancer and screening among women attending OPD in Sree Mookambika Institute Of Medical Sciences, Kulasekharam Methods: A cross sectional study was conducted among 133 women attending OPD. After obtaining informed consent, data were collected using a pretested questionnaire over three months and analyzed using SPSS. Results: Among 133 participants, 46.6% were married. Most (94%) had heard of cervical cancer, and 61.7% knew its symptoms, mainly abnormal vaginal bleeding (49.4%) and unusual discharge (31.3%). Only 25.6% had experienced such symptoms. The main information source was the internet (44%). About 75.2% were aware of HPV vaccination, and 49.6% believed women should undergo annual screening. Cost of services was cited as the main barrier (46.6%). The most recognized risk factor was HPV infection (68%). Education significantly influenced participants’ knowledge and attitudes, with higher education associated with better awareness of risk factors (p = 0.006), symptoms (p = 0.007), and a more positive attitude toward HPV vaccination (p = 0.007). Conclusion: Cervical cancer is preventable through timely screening and HPV vaccination. Education enhances awareness and preventive practices, while reducing service costs may improve screening uptake.